Cytotoxicity, dose-enhancement and radiosensitization of glioblastoma cells with rare earth nanoparticles - Victor M. Lu; Felicity Crawshay-Williams; Benjamin White; Amy Elliot; Mark A. Hill; Helen E. Townley (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Glioblastoma is a heterogeneous disease with multiple genotypic origins. Despite treatment protocols such as surgery, radiotherapy and chemotherapy, the prognosis for patients remains poor. This study investigates the cytotoxic and radiation dose-enhancing and radiosensitizing ability of five rare earth oxide nanoparticles, in two different immortalized mammalian cell lines; U-87 MG and Mo59K. Significant cytotoxicity was observed in U-87 MG cells when exposed to Nd2O3 and La2O3. Autophagy was also detected in cells after incubation with Nd2O3. Radiosensitization was observed in U-87 MG when incubated with Gd2O3, CeO2-Gd and Nd2O3:Si. Importantly, these elements did not cause any intrinsic toxicity in the absence of irradiation and so could be considered biocompatible. The Gd2O3 and CeO2-Gd nanoparticles were also seen to generate ROS in U-87 MG cells after irradiation. Furthermore, the Mo59K and U-87 MG cells responded very differently to exposure to the rare earth nanoparticles. This may indicate the importance of the genotype of cells in the successful use of rare earth oxides for treatment.